Decoding the interface: Exploring women's perspectives on integrating AI in professional work - Woźniak-Jęchorek, Beata; Rydzak, Waldemar; Kuźmar, Sławomir (Human Technology, 2023)
AI's impact on jobs varies by gender, with women facing higher replacement risks. This discrepancy is intensified by the digital divide, insufficient knowledge and skills, and a less open attitude towards AI among women, thereby limiting women's access to AI-driven opportunities. This paper's primary objective is to scrutinize women's self-assessment of digital competencies when utilizing AI in professional settings. Drawing from a survey conducted among Polish women, our findings reveal that the adoption of AI is linked to factors such as age, education, work experience, and location of residence. Women with higher levels of education residing in larger cities, as well as younger individuals with less work experience, are more likely to recognize the advantages of utilizing AI. Their concerns are less about the necessity for continuous development of digital skills, but rather about the potential impact of AI on their work-life balance and the possibility of a decrease in earnings, despite the anticipated improvements in productivity and time management efficiency.